2016
DOI: 10.2337/dc15-0991
|View full text |Cite
|
Sign up to set email alerts
|

An Inverse Relationship Between Age of Type 2 Diabetes Onset and Complication Risk and Mortality: The Impact of Youth-Onset Type 2 Diabetes

Abstract: OBJECTIVEThis study compared the prevalence of complications in 354 patients with T2DM diagnosed between 15 and 30 years of age (T2DM [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] ) with that in a durationmatched cohort of 1,062 patients diagnosed between 40 and 50 years (T2DM [40][41][42][43][44][45][46][47][48][49][50] ). It also examined standardized mortality ratios (SMRs) according to diabetes age of onset in 15,238 patients covering a wider age-of-onset range. RESEARCH DESIGN AND METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
152
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(174 citation statements)
references
References 24 publications
10
152
2
2
Order By: Relevance
“…Moreover, the high mortality rate may be due to the casual approach to T2DM which is evident from the medication data, only 57% of the T2DM subjects have followed the proper medication (table 3, insulin injection 6% and Oral Medicine 51%) schedule, table 1 and a huge undiagnosed population. This study is in agreement with other studies [39] also.…”
Section: Early Onset Of T2dmsupporting
confidence: 94%
“…Moreover, the high mortality rate may be due to the casual approach to T2DM which is evident from the medication data, only 57% of the T2DM subjects have followed the proper medication (table 3, insulin injection 6% and Oral Medicine 51%) schedule, table 1 and a huge undiagnosed population. This study is in agreement with other studies [39] also.…”
Section: Early Onset Of T2dmsupporting
confidence: 94%
“…The TODAY study showed that even with the resources to encourage consistent early lifestyle modification and the provision of medications for glycaemic control and aggressive ACE inhibitor therapy, the prevalence of both hypertension and microalbuminuria increased markedly over time among adolescents with type 2 diabetes regardless of diabetes treatment [6]. More recently a small study from Australia showed that those with diabetes who were diagnosed between 15 and 30 years of age had more severe albuminuria and neuropathy scores compared with those diagnosed at 40-50 years of age after adjustment for diabetes duration [22]. As such, increased clinical attention is imperative for individuals with earlieronset type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 This is in accordance with the degenerative character of diabetes, widely demonstrated in observational studies, even in non-elderly. 31,32 …”
Section: Discussionmentioning
confidence: 99%